2020
DOI: 10.1002/spe.2941
|View full text |Cite
|
Sign up to set email alerts
|

Software fault prediction using Whale algorithm with genetics algorithm

Abstract: Software fault prediction became an essential research area in the last few years, there are many prediction and optimization techniques that have been developed for fault prediction. In this paper, an approach is developed by integrating genetics algorithm with support vector machine (SVM) classifier and Whale optimization algorithm for software fault prediction. The developed approach is applied to 24 datasets (12‐NASA MDP and 12‐Java open‐source projects), where NASA MDP is considered as a large‐scale datas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The datasets cover 14 distinct software development projects based mainly on three programming languages: C, C++, and Java. The nature of those software systems from the same organization was also different, probably with distinct architectures and design patterns, since some were related to, for example, spacecraft instruments (CM1), a storage management system for receiving and processing ground data (KC1, KC2, and KC3), a combustion experiment of a space shuttle (MC1), a video guidance system (MC2), a zero-gravity experiment related to combustion (MW1), flight software from an earth-orbiting satellite (PC1, PC2, and PC4), s dynamic simulator for attitude control systems (PC2), and a cockpit security increase system (PC5) [59,60]. Finally, the original study used a dataset from a single NASA project, which the present one seeks to extend.…”
Section: Datasetmentioning
confidence: 99%
“…The datasets cover 14 distinct software development projects based mainly on three programming languages: C, C++, and Java. The nature of those software systems from the same organization was also different, probably with distinct architectures and design patterns, since some were related to, for example, spacecraft instruments (CM1), a storage management system for receiving and processing ground data (KC1, KC2, and KC3), a combustion experiment of a space shuttle (MC1), a video guidance system (MC2), a zero-gravity experiment related to combustion (MW1), flight software from an earth-orbiting satellite (PC1, PC2, and PC4), s dynamic simulator for attitude control systems (PC2), and a cockpit security increase system (PC5) [59,60]. Finally, the original study used a dataset from a single NASA project, which the present one seeks to extend.…”
Section: Datasetmentioning
confidence: 99%
“…The numerical results demonstrate that the proposed approach performs better on relatively large-scale complex problems. Alsghaier et al [138] developed an approach by integrating a genetic algorithm with a SVM classifier and WOA for software fault prediction. The results indicated that the developed approach was suitable for large and small-scale datasets.…”
Section: E Research Progress Regarding Theory and Applications Of Wha...mentioning
confidence: 99%
“…Results showed that IsBMFO, followed by support vector machine (SVM) classifcation, outperformed other models for the SDP problem, with an average G-mean of 78%. Alsghaier and Akour [60] developed an approach for software fault prediction by combining the genetics algorithm (GA) with the SVM classifer and WOA. It was then applied to 24 datasets, and the results confrmed the improved performance of the software fault prediction process.…”
Section: Applications Of Gwo Woa Hho and Mfo In Softwarementioning
confidence: 99%